Gender equality among medical and dental academic researchers in West Africa: a theoretical analysis of a compendium of research - Foláyan, Moréniké Oluwátóyìn; Gascón-Catalán, Ana; Martínez-Pérez, Guillermo Z. (Frontiers in Oral Health, 2025)
BackgroundThis study conducted theoretical analyses of the findings of a study on gender disparities in research productivity and leadership in medical and dental research institutions in Nigeria. The aim was to highlight the connectedness of the study findings, and to develop a conceptual framework that can inform future studies on gender equity in academia across West Africa.MethodsA content analysis of the research outputs was conducted using four theoretical frameworks to assess the alignment of the study findings with gender equality goals. The research examined policy effectiveness and institutional practices using the 2008 USAID Gender Equality Framework; analyzed how personal traits, societal expectations, and organizational practices intersect using Fagenson's Theory of Gender and Career Development; uncovered gendered power dynamics and inform strategies for institutional reform using the Feminist Institutionalism Analytical Lens; and shed light on disparities in mentorship, collaboration, and academic publishing using the Academic Literacies Theory.ResultsThe key domains influencing gender inequality and requiring targeted actions are: first, the patriarchal societal, cultural, and religious values that shape gender roles, restricting women's career advancement. Second, institutional policies and organizational culture that limits female leadership and research productivity. Third, individual and generational perspectives influence advocacy, with younger individuals recognizing inequality more readily. Research productivity and leadership disparities can be addressed through mentorship and training programs for early-career researchers that foster the development of gender-sensitive advocates. The developed conceptual framework outlines three core research and action domains—societal, institutional, and individual factors—and their sub-factors, alongside targeted interventions influencing gender inequality, proposed targeted recommendations and expected outcomes.ConclusionsThe findings emphasize the multifaceted nature of gender disparities. Strategic actions are needed to address the issues that foster gender equality in medical and dental research institutions, and to support female researchers in West Africa. These actions should focus on the younger generations to drive needed changes.